2021
DOI: 10.3389/fonc.2021.795568
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis of the Top-Cited Publications and Research Trends for Stereotactic Body Radiotherapy

Abstract: ObjectiveThis study aims to analyze the 100 most cited papers and research trends on stereotactic body radiotherapy (SBRT).MethodsWe used Web of Science to identify the 100 most frequently cited papers on SBRT on September 29, 2021 and extracted the following data: publication year, source title, country/region, organization, total citations, and average number of citations per year. The research type and research domain were classified independently by the authors. Then we carried out a bibliometric analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…A recent phase 3 randomized trial (IMpower 010) showed a disease-free survival benefit with atezolizumab versus best supportive care after adjuvant chemotherapy in patients with resected stages II–IIIA NSCLC; the benefit was more pronounced in the subgroup with PDL1 TPS ≥1% ( 61 ). The combination of stereotactic ablative radiotherapy (SABR) with immunotherapy (I-SABR) for NSCLC is a research hotspot ( 11 ). The PEMBRO-RT phase 2 randomized trial demonstrated that SABR prior to pembrolizumab for locally advanced NSCLC improved the prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent phase 3 randomized trial (IMpower 010) showed a disease-free survival benefit with atezolizumab versus best supportive care after adjuvant chemotherapy in patients with resected stages II–IIIA NSCLC; the benefit was more pronounced in the subgroup with PDL1 TPS ≥1% ( 61 ). The combination of stereotactic ablative radiotherapy (SABR) with immunotherapy (I-SABR) for NSCLC is a research hotspot ( 11 ). The PEMBRO-RT phase 2 randomized trial demonstrated that SABR prior to pembrolizumab for locally advanced NSCLC improved the prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a bibliometric analysis can objectively, comprehensively, and quantitatively evaluate a whole academic discipline based on the information and a citation network of the relevant publications ( 10 ). The visualization based on the bibliometric analysis (i.e., bibliographic coupling) can present the results in multiple forms, which are intuitive and comprehensible for readers ( 11 ). Moreover, publications that are important nodes in the citation network can be recognized, and benefit the authors in discussing the history and current status of the research area.…”
Section: Introductionmentioning
confidence: 99%
“…Data were obtained from the Science Citation Index Expanded (SCI-E) database in the Web of Science Core Collection (WOSCC) ( 1 ). The literature search was framed as follows: [TI = (Premenstrual Syndrome) OR TI = (Premenstrual Dysphoric Disorder) OR TI = (late luteal phase dysphoric disorder) referring to related retrieval strategy ( 16 ). The range of article publication dates range was set from inception of the database to April 8th, 2022.…”
Section: Methodsmentioning
confidence: 99%
“…Although this is the most commonly used database for literature searches, some early publications may be missing. For an accurate econometric analysis, we referred to previous studies ( 16 ) and adopted a Title keyword rather than Topic keyword retrieval approach. Although our search results were accurate, they may not be extensive enough.…”
Section: Limitationsmentioning
confidence: 99%
“…As a method for sorting published articles and establishing the citation relationship (ie, bibliographic coupling) between them, a bibliometric analysis can aid researchers to become familiar with the state of a research area ( 6 , 7 ). It is superior to review or meta-analysis in evaluating a whole academic discipline including thousands of publications ( 8 ).…”
Section: Introductionmentioning
confidence: 99%